Niche Differentiation at Multiple Spatial Scales on Large and Small Mediterranean Islands for the Endemic Silene velutina Pourr. ex Loisel. (Caryophyllaceae) - Valentina Murru; Emmanuele Farris; Andrea Santo; Oscar Grillo; Carole Piazza; Antonella Gaio; Gianluigi Bacchetta; John D. Thompson (Plants, 2021)
The aim of this work is to investigate niche variations in endemic Silene velutina (Caryophyllaceae, Angiosperms) on Mediterranean islands that differ in size. Six populations on both large and small islands were sampled across the geographic range of the species. For each population, 10 plots (1 × 2 m, with a 25 cm grill) were randomly placed to quantify environmental (abiotic and biotic factors and disturbance) and population (demographic structure and reproductive success) parameters. Niche parameters related to substrate, plant cover, community diversity and composition and disturbance showed significant variation in relation to island size. At the regional scale, we detected a broader niche on large islands associated with spatial heterogeneity and island size. In contrast, at the local scale, populations on small islands showed a broader niche, potentially due to a release from competition (low diversity and plant cover and absence of phanerophytes). Populations on large islands had a demographic structure biased towards vegetative individuals (seedlings and juveniles) with few reproductive individuals, while those on small islands had a majority of adults. Together, the results on niche breadth and demographic structure concord with the idea of a strategy based on adult persistence on small islands.